Reevaluating Inheritance Distribution in Indonesia: The Role of Hibah as a Preventive Measure - Bilalu, Naskur; Bukido, Rosdalina; Subeitan, Syahrul Mubarak; Zakariah, Asril Amirul (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This study examines the understanding of wealth distribution during the testator's lifetime under Article 187, paragraphs (1) and (2) of the Compilation of Islamic Law. The purpose is to understand the distribution of wealth during the testator's lifetime and the construction of the implementation of wealth distribution during the testator's lifetime as a legal option. This research employs a qualitative approach using juridical-normative methods. The data sources consist of articles in the Compilation of Islamic Law (KHI) that regulate Islamic law in Indonesia. The findings reveal that understanding wealth distribution during the testator's lifetime is a legal option based on two considerations: first, wealth distribution after the testator's death may lead to conflicts; second, it may cause unfairness among heirs. The construction of wealth distribution implementation involves three aspects: 1) verifying the estate of the deceased, 2) validating the expenses incurred by the testator, and 3) distributing wealth to the heirs through four legal options, namely: the testator and heirs agree to a settlement, the testator considers gifts previously given to the heirs as part of the inheritance, the testator revokes gifts previously given to their children, and the testator distributes the inheritance according to the provisions of inheritance law.